2008
DOI: 10.1590/s0103-90162008000700011
|View full text |Cite
|
Sign up to set email alerts
|

Solar radiation affects grapevine susceptibility to Plasmopara Viticola

Abstract: Solar radiation plays an important role in the development of some fungal diseases due to its direct action on the microorganisms and also its indirect effect on the production of specific plant compounds. This experiment examined the effect of two light environments (100% and 35% of full strength) on the polyphenolic content of grapevine leaves and quantified their relation to resistance to downy mildew (Plasmopara viticola). Leaf epidermal polyphenolic contents were non-destructively measured during the grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…In our studies with okra, we have found no effect of a high nitrogen application (administered daily instead of weekly) on flavonoids independent of the UV treatments (data not shown). Higher flavonoid concentrations have also been found to be associated with improved defense against pathogens in some species (e.g., grapevine) (Agati et al, 2008;Dalla Marta et al, 2008), but this was addressed in our study. We did find, however, that leaf age and surface (abaxial vs. adaxial) were factors that affected UV-absorbing compound concentrations in the leaf.…”
Section: Discussionmentioning
confidence: 79%
“…In our studies with okra, we have found no effect of a high nitrogen application (administered daily instead of weekly) on flavonoids independent of the UV treatments (data not shown). Higher flavonoid concentrations have also been found to be associated with improved defense against pathogens in some species (e.g., grapevine) (Agati et al, 2008;Dalla Marta et al, 2008), but this was addressed in our study. We did find, however, that leaf age and surface (abaxial vs. adaxial) were factors that affected UV-absorbing compound concentrations in the leaf.…”
Section: Discussionmentioning
confidence: 79%
“…Both UV-A and UV-B are able to increase flavonoid levels, but UV-B has stronger efficacy [49]. However, there are also other factors influencing flavonoid content, for example, negative correlations with nitrogen concentrations and pathogen infestation [50][51][52][53]. This highlights the regulatory effect that UV radiation has on plant mechanisms as presented by flavonoid glycosides and hydroxycinnamic acids here.…”
Section: Flavonoidsmentioning
confidence: 86%
“…Atmospheric phenomena also bring a considerable influence over mandatory stages related to crop development and management, too. Solar energy is relevant for all stages of crop development, from seed germination to flowering/fruiting, and its effects can be either positive or negative [5][6][7][8]. Green plants use photosynthetically active radiation (PAR) for photosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[9]. Regarding grapevine leaves' resistance to downy mildew (Plasmopara viticola), the leaves receiving 100% solar radiation should have fewer mildew problems than the shadowed leaves [6]. Solar radiation also has a significant role in evaporation and transpiration evaporation processes and, since they are interconnected, the common term to express them is crop evapotranspiration (crop ET) [10].…”
Section: Introductionmentioning
confidence: 99%